Credit growth and countercyclical capital buffers: Empirical evidence from Central and Eastern European countries - Adam Geršl; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2012)
Excessive credit growth is often considered to be an indicator of future problems in the financial sector. This paper examines the issue of how to determine whether the observed level of private sector credit is excessive in the context of the countercyclical capital buffer, a macroprudential tool proposed in the new regulatory framework of Basel III by the Basel Committee on Banking Supervision. An empirical analysis of selected Central and Eastern European countries, including the Czech Republic, provides alternative estimates of excessive private credit and shows that the HP filter calculation proposed by the Basel Committee is not necessarily a suitable indicator of excessive credit growth for converging countries.
Keywords: G01; G18; G21; 330; Basel regulation; credit growth; financial crisis countercyclical buffer